Community health workers at the dawn of a new era: 6. Recruitment, training, and continuing education - Meike J. Schleiff; Iain Aitken; Mohammad Ariful Alam; Zufan Abera Damtew; Henry B. Perry (BMC, 2021)
Abstract Background This is the sixth of our 11-paper supplement entitled "Community Health Workers at the Dawn of New Era". Expectations of community health workers (CHWs) have expanded in recent years to encompass a wider array of services to numerous subpopulations, engage communities to collaborate with and to assist health systems in responding to complex and sometimes intensive threats. In this paper, we explore a set of key considerations for training of CHWs in response to their enhanced and changing roles and provide actionable recommendations based on current evidence and case examples for health systems leaders and other stakeholders to utilize. Methods We carried out a focused review of relevant literature. This review included particular attention to a 2014 book chapter on training of CHWs for large-scale programmes, a systematic review of reviews about CHWs, the 2018 WHO guideline for CHWs, and a 2020 compendium of 29 national CHW programmes. We summarized the findings of this latter work as they pertain to training. We incorporated the approach to training used by two exemplary national CHW programmes: for health extension workers in Ethiopia and shasthya shebikas in Bangladesh. Finally, we incorporated the extensive personal experiences of all the authors regarding issues in the training of CHWs. Results The paper explores three key themes: (1) professionalism, (2) quality and performance, and (3) scaling up. Professionalism: CHW tasks are expanding. As more CHWs become professionalized and highly skilled, there will still be a need for neighbourhood-level voluntary CHWs with a limited scope of work. Quality and performance: Training approaches covering relevant content and engaging CHWs with other related cadres are key to setting CHWs up to be well prepared. Strategies that have been recently integrated into training include technological tools and provision of additional knowledge; other strategies emphasize the ongoing value of long-standing approaches such as regular home visitation. Scale-up: Scaling up entails reaching more people and/or adding more complexity and quality to a programme serving a defined population. When CHW programmes expand, many aspects of health systems and the roles of other cadres of workers will need to adapt, due to task shifting and task sharing by CHWs. Conclusion Going forward, if CHW programmes are to reach their full potential, ongoing, up-to-date, professionalized training for CHWs that is integrated with training of other cadres and that is responsive to continued changes and emerging needs will be essential. Professionalized training will require ongoing monitoring and evaluation of the quality of training, continual updating of pre-service training, and ongoing in-service training-not only for the CHWs themselves but also for those with whom CHWs work, including communities, CHW supervisors, and other cadres of health professionals. Strong leadership, adequate funding, and attention to the needs of each cadre of CHWs can make this possible.